SURGICAL MANAGEMENT IN ESOTROPIA AT CIPTO MANGUNKUSUMO HOSPITAL: A 4-YEAR OBSERVATION ON CHARACTERISTIC AND RESULT - Fauzia, Firdha Malisa; Bani, Anna Puspitasari (Majalah Oftalmologi Indonesia, 2024)
Introduction: Esotropia, although have low prevalence in Indonesia, give significant impacts on its sufferer, and due to the wide range of types creates numerous options for surgery without much consensus. Success rates of the surgery also varied depends on many factors. This study aims to evaluate clinical characteristics, success rate in esotropia surgery, and factors that may influence the outcome. Methods: A retrospective descriptive study based on secondary data from medical records of child and adult esotropia patients who underwent surgery from January 2018 to December 2021. Result: Of 68 patients included in the study, 60.2% were adults. More than half of patients have an onset before 7 years of age, though amblyopia only affects 29.4% of patients. Squinted-eye was the chief complaint in most patients (76.5%). One-third of patients had basic type esotropia and 59.7% had large preoperative deviation. Unilateral procedure was done in 50% of patients. The surgery success rate reached 65% with good stability on 8 months of follow-up. Better results were seen in congenital and basic type esotropia than in other types. Although none of the believed influenced factors affecting outcome were significant statistically, duration <5 years and preoperative deviation <50 PD had a higher success rate of 75% and 84.6%. Conclusion: Esotropia surgery in Cipto Mangunkusumo hospital were performed majorly in adults with large pre-operative deviations, mostly by unilateral procedure of recession and resection. The surgeries yield good results and stability, with shorter duration and smaller preoperative deviation giving higher success rates.